Introduction to Molecular Biology Working with DNA and RNA - Ableitner, Oksana (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2022)
Oksana Ableitner offers a practical, clearly structured and easy to understand introduction to complicated definitions and structures in chemistry and molecular biology for work in the molecular biology laboratory. The author is guided by her experience in working with students and uses many illustrations to visualize abstract knowledge. An understanding of this matter is an essential basis for successful work with DNA and RNA in order to ensure high quality results. For responsible activities in application - such as genetic research or the determination of various pathogens - it is essential to be confident in dealing with the basics of these sensitive, fast and specific analytical methods. This Springer essential is a translation of the original German 2nd edition essentials, Einführung in die Molekularbiologie by Oksana Ableitner, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2018. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The content Basic concepts of molecular biology Molecular biological methods such as PCR, real-time PCR, gel electrophoresis, sequencing, MLST, microarray technology and PFGE Chemical calculation in the laboratory The target groups Students of biology, chemistry and medicine Medical and chemical-technical assistants, biomedical analysts The Author After studying chemistry and biology, Oksana Ableitner first worked as a teacher in a Ukrainian school. After further training as a chemical engineer in Graz, she has worked for many years in the Core Unit Molecular Biology at a laboratory in Graz and is responsible for the implementation and optimisation of various molecular biological processes. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Basic concepts of molecular biology -- Molecular biology methods such as PCR, real-time PCR, gel electrophoresis, sequencing, MLST, microarray technology and PFGE -- Chemical computing in the laboratory.
Keywords: Molecular biology; Biology-Technique.; Chemistry, Organic; Medical genetics; Molecular Biology; Biological Techniques; Organic Chemistry; Medical Genetics